Factors affecting farmers' willingness to adopt salt-tolerant forage crops in south-eastern Tunisia - Chebil, A.; Nasr, H.; Zaibet, L. (2009)
This paper analyzed the factors that affect farmers’ willingness to adopt salt-tolerant forage for livestock, using a Tobit model. The data used for the empirical analysis was obtained from a survey of 97 farmers in southeastern Tunisia. The results of this study show that variables related to age, education level, the salinity level of water and membership in a farmers’ association do not significantly influence the degree to which salt-tolerant forage production is adopted. It did, however, find a positive relationship between off-farm income availability and adoption. In addition, the flock size variable, expressed in Standard Livestock Units, has a significant and positive relationship with adoption. This indicates farmers’ need to cover their forage deficit. Agricultural extension services should ensure that the requisite forage species are made available, and work with farmers to encourage them to adopt salt-tolerant forage species and pass on their knowledge to other farmers.